A Robust Mobile-Based Incident Reporting System - Opoku, Samuel King; Mohammed, Humu (IJRDO -Journal of Computer Science Engineering, 2017)
With the rampant occurrences of crime, societies have various methods for alerting the police when a crime strikes. Currently in many countries, report to the police occurs after the crime. The reporters are asked to make full statement that includes everything they can remember about the incident. The police then embark on investigation and they may or may not arrest the victim. In well-established organizations, buttons are installed which are pressed to notify the police in case of emergency. However, the buttons may be at far distance to be pressed during the incident. The use of a mobile phone is not limited to talking alone it is being used in making video, recording information and transmitting it to a phone or a computer as was being done by a computer. This paper develops an incident reporting system that uses mobile phone and wireless communication technology. The user at the crime screen long presses a key and a message from the client’s phone is sent to the receiving phone be a police system or guardian system stating the location of the user. The paper also analyses the various wireless communication technology used in mobile communication technology determining their pros and cons